2020
DOI: 10.3390/app10113906
|View full text |Cite
|
Sign up to set email alerts
|

Climate-Smart Agro-Hydrological Model for a Large Scale Rice Irrigation Scheme in Malaysia

Abstract: Agro-hydrological water management frameworks help to integrate expected planned management and expedite regulation of water allocation for agricultural production. Low production is not only due to the variability of available water during crop growing seasons, but also poor water management decisions. The Tanjung Karang Rice Irrigation Scheme in Malaysia has yet to model agro-hydrological systems for effective water distribution under climate change impacts. A climate-smart agro-hydrological model was develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…The use of satellite imagery as a data source in urban planning also helps identify climate-friendly solutions (Milojevic-Dupont et al, 2020). Web-based water management (Mourtzios et al, 2021) can be supported with trends identified from time-series data (Ise et al, 2020), but remotely sensed water flow data also complements the agricultural water management model (Ismail et al, 2020). And if we increase the resolution of the data (Jimenez et al, 2019), we can also understand the causal relationships related to consumption.…”
Section: The Importance Of the System Of Systems Approachmentioning
confidence: 99%
See 4 more Smart Citations
“…The use of satellite imagery as a data source in urban planning also helps identify climate-friendly solutions (Milojevic-Dupont et al, 2020). Web-based water management (Mourtzios et al, 2021) can be supported with trends identified from time-series data (Ise et al, 2020), but remotely sensed water flow data also complements the agricultural water management model (Ismail et al, 2020). And if we increase the resolution of the data (Jimenez et al, 2019), we can also understand the causal relationships related to consumption.…”
Section: The Importance Of the System Of Systems Approachmentioning
confidence: 99%
“…Agricultural satellite imagery applications (Majidi et al, 2021) can be transferred to air quality satellite monitoring (Semlali and El Amrani, 2021), or time-series data (Ise et al, 2020) can be used to plan better agricultural interventions. By implication, satellitebased support plays an important role in modeling agricultural water management (Ismail et al, 2020), but disaster news (Park et al, 2020) also helps provide a deeper understanding of social involvement. In assessing disaster resilience in different areas, (Sasaki et al, 2020) satellite imagery provides feedback on risks that can even be revealed over time (Joshi et al, 2019).…”
Section: The Importance Of the System Of Systems Approachmentioning
confidence: 99%
See 3 more Smart Citations